Onconeural antibody-associated cerebellar ataxia: An analysis - Rohan Mahale; Sandeep M; Anitha Mahadevan; Nitish Kamble; Vikram Holla; Pramod K. Pal; Ravi Yadav (Annals of Movement Disorders)
BACKGROUND: Cohort-based studies on onconeural antibody-associated cerebellar ataxia (CA) investigating the immunological and radiological spectrum as well as functional outcomes are limited. OBJECTIVE: To study the clinical, radiological, and immunological spectrum, as well as the treatment profile and outcomes, of onconeural antibody-associated CA. METHODS: A retrospective descriptive analysis was performed for a cohort of patients who presented with CA and had positive onconeural antibodies in serum. The clinical, radiological, and immunological spectrum and the treatment profile and outcomes of the patients were analyzed. RESULTS: Thirty-two patients were diagnosed with onconeural antibody-associated CA and were selected for our analysis. Eighteen patients (56%) had anti-Yo, seven (22%) had anti-Zic4, four (12.5%) had anti-CV2/CRMP5, two (6.25%) had anti-Hu, and one had anti-PCA-2 antibodies. The median duration of illness was 4 months (interquartile range (IQR): 3–6 months). Twenty-eight patients had pancerebellar syndrome. The mean score of the Scale for the Assessment and Rating of Ataxia (SARA) was 23.9 ± 5.2 (range: 16–34; median: 26). Bilateral cerebellar atrophy was observed in 24 patients (75%). Four patients with anti-Yo antibodies had breast lesions on screening at the time of admission. Two patients with anti-Yo antibodies had carcinoma ovary at 1-year follow-up. The median modified Rankin scale (mRS) score at admission was 4. Twelve patients underwent a 6-month follow-up (37%) and eight had a 1-year follow-up. Favorable outcomes (mRS scores ≤ 2) were observed in five patients (42%), whereas poor outcomes were observed in seven patients (58%). CONCLUSION: CA was most commonly caused by anti-Yo antibodies, followed by anti-Zic4 antibodies. Patients with anti-Zic4 antibodies had the lowest mean SARA score and the most favorable functional outcome. Patients with anti-Yo had poor functional outcomes with immunotherapy.